A Brief Note on the Magnetowetting of Magnetic Nanofluids on AAO Surfaces - Yu-Chin Chien; Huei Chu Weng (Nanomaterials, 2018)
In magnetowetting, the material properties of liquid, surface morphology of solid, and applied external field are three major factors used to determine the wettability of a liquid droplet on a surface. For wetting measurements, an irregular or uneven surface could result in a significant experimental uncertainty. The periodic array with a hexagonal symmetry structure is an advantage of the anodic aluminum oxide (AAO) structure. This study presents the results of the wetting properties of magnetic nanofluid sessile droplets on surfaces of various AAO pore sizes under an applied external magnetic field. Stable, water-based magnetite nanofluids are prepared by combining the chemical co-precipitation with the sol-gel technique, and AAO surfaces are then generated by anodizing the aluminum sheet in the beginning. The influence of pore size and magnetic field gradient on the magnetowetting of magnetic nanofluids on AAO surfaces is then investigated by an optical test system. Experimental results show that increasing the processing voltage of AAO templates could result in enhanced non-wettability behavior; that is, the increase in AAO pore size could lead to the increase in contact angle. The contact angle could be reduced by the applied magnetic field gradient. In general, the magnetic field has a more significant effect at smaller AAO pore sizes.